The impact that the influenza A (H1N1) pandemic had on news reporting in the state of Paraná, Brazil - Sandra Mara Maciel-Lima; José Miguel Rasia; Rodrigo Cechelero Bagatelli; Giseli Gontarski; Máximo José D. Colares (História, Ciências, Saúde: Manguinhos)
This study aims to analyze how influenza A (H1N1) in 2009 was reported in the state of Paraná. A total of 189 articles were analyzed in two newspapers from Paraná. Pursuant to analysis, four themes were identified: the spread of the virus; the pandemic and fear; influenza in the health service; and influenza in public policies. By studying how influenza A was reported in the media, it was possible to see the social impact that the H1N1 pandemic represented for society, presenting challenges for public institutions and ordinary citizens, who sensed that they were in a high-risk group exposed to a potentially lethal virus. This disease radically changed the habits of a globalized community seeking to escape from vulnerability.